Lost in space - an exploration of help-seeking among young people with mental health problems: a constructivist grounded theory study - Westberg, Katrin Häggström (Arch Public Health, 2020)
BACKGROUND: Mental health problems among young people is a worldwide public health concern. There has been an increase in mental health problems among young people in the Nordic countries in the last 25 years, particularly in Sweden. Despite this increase, international research has repeatedly shown that young people do not access or receive support when encountering mental health problems. The purpose of this study was to explore the process of help-seeking for professional support among young people with mental health problems. METHODS: The study used qualitative constructivist Grounded Theory and open-ended interviews. Thirteen young people between 15 and 23, recruited from two local support clinics, were interviewed. RESULTS: Lost in space emerged as the core category, capturing aspects of both the experience of self and mental health problems as well as the process of seeking and acquiring help from professional support systems. The study identified several prominent barriers for seeking and acquiring professional help for mental health problems. The young people expressed a lack of knowledge on mental health issues and support services and substantial efforts were made to try to cope with problems on one’s own. Lost in space involved Drifting - trying to make sense of own experiences and struggling to cope with problems, Navigating - searching for help through multiple attempts and contacts and Docking - finding support with something/somebody that feels right. CONCLUSIONS: The theoretical model sheds light on how young people with mental health problems were met with fragmented support services. Society needs to provide encompassing, youth-friendly and flexible support services, so that attempts at help-seeking are not missed.